Colorectal Cancer: Molecular Mutations and Polymorphisms - Sameer, Aga S. (Frontiers in Oncology, 2013)
Colorectal cancer (CRC) is one of the major causes of mortality and morbidity, and is the third most common cancer in men and the second most common cancer in women worldwide. The incidence of CRC shows considerable variation among racially or ethnically defined populations in multiracial/ethnic countries. The tumorigenesis of CRC is either because of the chromosomal instability (CIN) or microsatellite instability (MIN) or involving various proto-oncogenes, tumor suppressor genes and also epigenetic changes in the DNA. In this review I have focused on the mutations and polymorphisms of various important genes of the CIN and MIN pathways which have been implicated in the development of CRC.